The growth of plants containing pyrrolizidine alkaloids (PAs) in plots cultivated with medicinal aromatic plants (MAPs) and in their natural wild habitats in Kosovo - Fadil MILLAKU; Agim RYSHA; Naim BERISHA (Acta Agriculturae Slovenica)
Thousands of plant species worldwide produce about 600 different pyrrolizidine alkaloids (PAs), which are known to cause disease in humans and animals. The plants known for their  PAs content were investigated in 70 plots cultivated with 19 MAPs species and the natural habitats of 20 wild MAPs species. Most of the poisonous plants found in cultivated and the natural habitats of wild MAPs belong to the families of Asteraceae and Boraginaceae. In the cultivated MAPs plots, 22 plant species known for their PAs content were identified, including 7 from the Asteraceae, 13 from the Boraginaceae, and 1 species from the Convolvulaceae and Solanaceae families. 34 species known for their PAs content were identified in natural habitats, 17 of which belonged to the Boraginaceae and 15 to the Asteraceae families. Convolvulaceae and Solanaceae families were represented by only one species each. Most species from the Asteraceae family known for their PAs content identified in cultivated fields and natural habitats were from the genera Senecio and Jacobaea, while genera Myosotis, Pulmonaria and Symphytum from Boraginaceae family. In the plots cultivated with MAPs, Convolvulus arvensis L. known for its PAs content and tropane alkaloids (TAs) was the most prevalent.